A good knight's sleep (London : Simon and Schuster, 2013)
"Mike the Knight doesn't want to go to bed, there's too many knightly things to do! Will Mike learn that a good knight needs to sleep as well as practise?"--Cover.
On board pages.
Keywords: Children's stories